2021
DOI: 10.1530/ec-20-0509
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent sex differences in calcium and phosphate homeostasis

Abstract: Background: Sex differences in calcium and phosphate have been observed. We aimed to assess a relation with age. Methods: We used laboratory values of serum calcium, phosphate and albumin from three different samples (years 2005, 2010 and 2014) using the hospital information system of Erasmus MC, Rotterdam. The samples were divided into 3 age groups: 1-17, 18-44 and ≥45 years. Sex differences in calcium and phosphate were analyzed using ANCOVA, adjusting for age and serum albumin. Furthermore, sex by age int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 30 publications
5
15
0
Order By: Relevance
“…Our study found a gender difference in inorganic phosphate levels, with females in both diabetic and non-diabetic groups having higher serum inorganic phosphate levels than males. This sex difference in inorganic phosphate metabolism has been reported in different studies (Koek et al, Dominguez et al and Schwarz et al) [ [23] , [24] , [25] ].…”
Section: Discussionsupporting
confidence: 72%
“…Our study found a gender difference in inorganic phosphate levels, with females in both diabetic and non-diabetic groups having higher serum inorganic phosphate levels than males. This sex difference in inorganic phosphate metabolism has been reported in different studies (Koek et al, Dominguez et al and Schwarz et al) [ [23] , [24] , [25] ].…”
Section: Discussionsupporting
confidence: 72%
“…Some studies report similar phosphate levels in plasma in women and men [16], whereas other report women having slightly higher phosphate levels [31]. Other found higher phosphate levels in women aged over 45 years than men [32,33]. Of note, major differences exist how blood samples were collected (e.g., fasted vs. nonfasted, timed collection vs. random) that likely impact outcomes as phosphate levels, as well as the levels of hormones regulating phosphate bal- ance show circadian rhythms [34].…”
Section: Discussion/conclusionmentioning
confidence: 98%
“…Interestingly, women were overrepresented in the highest phosphate tertile in our study. Previous studies consistently report that postmenopausal woman have higher phosphate levels, compared to age-matched men, and suggested that declining estrogen levels after menopause causes sex differences in calcium and phosphate levels [ 25 ]. Adjustment for gender did not materially change the results, and we also found no effect modification by gender.…”
Section: Discussionmentioning
confidence: 99%